Pengaruh Prenatal Yoga Terhadap Kesiapan Psikologis Ibu Hamil Primigravida Trimester Iii Di Bidan Titin Kota Bekasi Tahun 2023 - Farida M Simanjuntak; friska junita; Nanda Nurvita Sari (Indonesian Journal of Midwifery Scientific, 2024)
Abstract The Influence of Prenatal Yoga on the Psychological Readiness of Primigravida Pregnant Women in the Third Trimester at Midwife Titin Bekasi City in 2023 Nanda Nurvita Sari¹, Farida M Simanjuntak²*, Friska Junita³ Midwifery study program (S1) and midwife professional education Indonesian Medical STIKes Jl. Cut Mutia Raya no 88A sepanjang jaya nurvitananda@gmail.com,faridams81@gmail.com*,friskajunita86@gmail.com Background: Psychological conditions during pregnancy will affect pregnancy and childbirth, especially many psychological problems, including anxiety and stress during pregnancy which can cause complications for the mother and baby. Practicing yoga during pregnancy can condition you physically and psychologically to become stronger and stronger but still flexible and flexible in adapting to various situations. Research objective: to find out whether there is an influence of mental yoga on the psychological readiness of third trimester primigravida pregnant women at PMB Midwife Titin Am.keb city of Bekasi.Research method: This type of research uses a quasi-experimental research design with one group pretest-posttest without control. The population in this study was all third trimester pregnant women, totaling 32 people, with a sampling technique using purposive sampling with inclusion and exclusion criteria. Research results: The increase in adrenaline hormone during prenatal yoga can give pregnant women energy to prepare physically and psychologically. Conclusion: The results of the study show that there is a significant influence between prenatal yoga and the psychological readiness of third trimester primigravida pregnant women (P=0.003). Suggestion: It is hoped that this research People can take part in prenatal yoga carried out by local health workers to be more psychologically prepared. Keywords: Prenatal Yoga, Primigravida, Psychological Readiness